2019
DOI: 10.1021/acsanm.9b01374
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Nanobioelectronics for Electrical Intracellular Sensing

Abstract: In order for the field of bioelectronics to make an impact on healthcare, there is an urgent requirement for the development of "wireless" electronic systems to both sense and actuate cell behaviour. Herein we report the first example of an innovative intracellular wireless electronic communication system. We demonstrate that chemistry can be electrically modulated in a "wireless" manner on the nanoscale at the surface of conductive nanoparticles uptaken by cells at unreported low potentials. The system is mad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…One reason why lower driving voltage is required at the nanoscale, especially, for electrodes with a radius below 50nm, is that the diffuse double layer extending from the CNTPs bipolar electrodes into the solution becomes significant 46 , and dramatically increases the capacitance associated with the charging current and at the CNTPs. Our observation of lower voltages required to initiate wireless electrochemistry at the nanoscale are also supported by our previous work on nano-BPEs 54 .…”
Section: ∆ E Elec =E Tot ( L Elec L Channel )supporting
confidence: 88%
“…One reason why lower driving voltage is required at the nanoscale, especially, for electrodes with a radius below 50nm, is that the diffuse double layer extending from the CNTPs bipolar electrodes into the solution becomes significant 46 , and dramatically increases the capacitance associated with the charging current and at the CNTPs. Our observation of lower voltages required to initiate wireless electrochemistry at the nanoscale are also supported by our previous work on nano-BPEs 54 .…”
Section: ∆ E Elec =E Tot ( L Elec L Channel )supporting
confidence: 88%
“…In view of that, we demonstrated that biocompatible and conductive gold nanoparticles under external electrical input can be used as electrical transducers to not only sense but also to modulate chemistry inside cells. [240,241] However, to alter the electrical behavior in cancer cells, ideally, we need devices that not only sense the electrical state of the cells, but which can also actuate it. Moreover, due to the inherent three dimensionalities of biological systems, we are also likely to require new manufacturing capabilities for 3D bioelectronics.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…The number of GNPs inside each cell was determined using the method reported earlier. [3] Colorimetric Caspase-3 assay: For caspase-3 detection, two different approaches were studied.…”
Section: Cellular Uptake Analysismentioning
confidence: 99%
“…[2] The advancement of NP-protein conjugates for sensing, imaging, drug delivery and targeting is of interest for many diverse applications. [3] In particular, the NPprotein conjugates are regarded as new innovative therapeutic agents. [4] Upon conjugation to NPs, therapeutic proteins can be delivered specifically at a desired targeted site.…”
Section: Introductionmentioning
confidence: 99%